An electrochemical sensor for creatinine based on carbon nanotubes/folic acid /silver nanoparticles modified electrode. (15th October 2020) - Fekry, A.M.; Abdel-Gawad, S.A.; Tammam, R.H.; Zayed, M.A.
Graphical abstract: Highlights: Carbon nanotubes/folic acid /silver nanoparticles modified carbon paste electrode was created for creatinine sensing. The modified sensor displayed excellent performance with detection limit of 0.008 µM. The sensors exhibit a fast response of 1.5 s. The sensor was effective for determination of creatinine in human urine. Abstract: A sensitive electrochemical sensor was developed by modifying a carbon paste electrode (CPE) with silver nanoparticles (AgNPs)/multi walled carbon nanotube (CNT)/folic acid (FA) for the improved detection of creatinine. The sensor demonstrated high electrocatalytic activity to the oxidation of creatinine in universal buffer solution. Scanning electron microscopy (SEM) and Energy dispersive X-Ray analysis (EDX) were employed for studying the surface morphology. Cyclic voltammetry (CV), differential pulse voltammetry (DPVs), chronoamperometry (CA) and electrochemical impedance spectroscopy (EIS) were utilized to study the electrocatalytic activity of the sensor. The electrode exhibited a good selectivity, stability and fast response (1.5 s) over a range of concentration (1 × 10 −8 to 2 × 10 −4 M) for creatinine at pH 7.0 giving a detection limit of 0.008 µM. Real aliquot exploration was done utilizing human urine and serum. The constructed sensor has proved to be very effective in evaluating the creatinine in terms of low detection limit, high sensitivity and reproducibility.